2022
DOI: 10.1002/smll.202203678
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Nanocarriers Based Drug Delivery Technology for Blood‐Brain Barrier Crossing and Brain Tumor Targeting Therapy

Abstract: His research interests include translational studies in the development of new therapies and biomarkers for prognosis and prediction of therapy, and mechanism investigation of treatment resistance in lymphoma. Yinyan Wang is a neurosurgeon and doctoral supervisor at Beijing Tiantan Hospital, and he is a principal investigator for the National Research Center of Neurological Diseases, a principal investigator for China Institute for Brain Research, Beijing. He focused on the individualized precise treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 324 publications
0
17
0
Order By: Relevance
“…37 A dual-targeted slow-release delivery microsphere for Glypican-3 (GPC3) and EpCAM not only specifically targets HCC cells, but also serves as a potential MRI contrast agent. 38 In addition, IOE particles containing iron oxide were detectable by dedicated MRI imaging during intra-arterial injection in an animal model of HCC. 39 Dual-specific MRI molecular probes for HCC, results of in vitro studies demonstrated higher targeting efficiency and MRI sensitivity of dual-specific probes for HCC cells compared to single-targeted or non-targeted molecular probes.…”
Section: Discussionmentioning
confidence: 98%
“…37 A dual-targeted slow-release delivery microsphere for Glypican-3 (GPC3) and EpCAM not only specifically targets HCC cells, but also serves as a potential MRI contrast agent. 38 In addition, IOE particles containing iron oxide were detectable by dedicated MRI imaging during intra-arterial injection in an animal model of HCC. 39 Dual-specific MRI molecular probes for HCC, results of in vitro studies demonstrated higher targeting efficiency and MRI sensitivity of dual-specific probes for HCC cells compared to single-targeted or non-targeted molecular probes.…”
Section: Discussionmentioning
confidence: 98%
“…They can improve the water-solubility of drugs, increase targeting ability, [10] and achieve controlled drug release, promoting these anticancer drugs to accumulate in tumor cells and avoiding the toxicity to normal cells. [11][12][13] In addition, nanomedicines are larger than small molecule drugs by ten times, which can minimize kidney filtration, prolong circulation time in the blood, and increase their tumor accumulation. Among the numerous nano-drug delivery systems, dendrimers have received extensive attention due to their dispersibility and abundant surface functional groups which can be modified.…”
Section: Introductionmentioning
confidence: 99%
“…Untethered micro-nano robots are expected to be the next generation of minimally invasive therapeutic instruments in biomedicine, serving as powerful medical vehicles that can access hard-to-reach areas of the body to perform least-invasive procedures and drug delivery [ 1 3 ]. The motions of microrobots in liquid media are at a low Reynolds number condition, and according to the scallop theorem [ 4 , 5 ], movement in such a super-viscous environment requires the breaking of the time-reversal symmetry of the kinetic patterns. Many noncontact microrobot-driven modalities, such as photoelectric driving [ 6 ], ultrasounds [ 7 ], magnetic fields [ 8 ], and their combinations [ 9 ], have been reported.…”
Section: Introductionmentioning
confidence: 99%